The heritability of Nematodirus battus fecal egg counts. Issue 4 (26th April 2022) - Nikbin, Saeid; Almasi, Fazel; Alenizi, Dalal; Jenvey, Caitlin; Sloan, Sarah; Preston, Sarah; Piedrafita, David; Jonsson, Nicholas; Stear, Michael
Abstract: Abstract: Although Nematodirus battus is a serious threat to the health and survival of young lambs, there are few options to control this parasite. Bayesian Monte Carlo Markov Chain modelling with a zero-inflated Poisson distribution was used to estimate the heritability of egg counts in both June and July for each of five consecutive cohorts of 200 Scottish Blackface lambs. In one of the 10 analyses, the results failed the diagnostic tests. In seven of the analyses, there was no convincing evidence that the variation in egg counts was heritable. In the 2 years of high infection, the heritability was approximately 0.4 in June but the estimates lacked precision and the 95% highest posterior density credible intervals ranged from just above zero to 0.7. Selective breeding for resistance to N. battus will be difficult because genetically resistant or susceptible lambs cannot be consistently identified by phenotypic markers.